Treatment of Anisometropic Amblyopia in children with refractive correction - Kaphle, D; Shrestha, JB; Paudel, P (Journal of Institute of Medicine Nepal, 2010)
Background: The main purpose of the study is to determine the effectiveness of spectacles alone in the treatment of anisometropia in paediatric population. Methods: A hospital based prospective study was conducted on twenty children (involving twenty-six eyes) with freshly diagnosed anisometropic amblyopia of mild to moderate grade. Optimal refractive correction was provided with spectacles alone and was followed at every 3 weeks until amblyopia resolved. Results: The mean line of improvement in visual acuity in 3 weeks was 0.85 ± 0.65 snellen lines. The mean line improvement in second follow up was 0.80 ± 0.70 lines. There was statistically significant (p=0.04) decrease in inter-ocular acuity (IOD) for anisometropia of 1 to 2.0D. The IOD improvement was associated with age (1.53 snellen lines in more than 8 years) in first follow up (p=0.001). IOD also decreased in children of more than 8 yrs. Conclusions: As in nearly half of the participants, especially who has minimal interocular acuity difference, anisometropic amblyopia resolved to normal acuity within first three weeks, we can conclude that the early improvement of visual acuity is related to lesser amount of anisometropia, age and sex. Key words: Anisometropic amblyopia, amblyopia resolution, inter-ocular difference (IOD), refractive correction The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 14-18